2007
DOI: 10.1103/physreve.76.057103
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synchronizability via age-based coupling

Abstract: In this brief report, we study the synchronization of growing scale-free networks. An asymmetrical age-based coupling method is proposed with only one free parameter α. Although the coupling matrix is asymmetric, our coupling method could guarantee that all the eigenvalues are non-negative reals. The eigneratio R will approach to 1 in the large limit of α.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In ref. [22], the ballistic diffusion is observed when the noise is in the region of green noise for small τ 2 and large τ 1 . In the following discussion, the noise is chosen in such a region to find whether the anomalous diffusion can also be found in the model of active Brownian particles.…”
Section: Dynamical Modelmentioning
confidence: 90%
See 1 more Smart Citation
“…In ref. [22], the ballistic diffusion is observed when the noise is in the region of green noise for small τ 2 and large τ 1 . In the following discussion, the noise is chosen in such a region to find whether the anomalous diffusion can also be found in the model of active Brownian particles.…”
Section: Dynamical Modelmentioning
confidence: 90%
“…There are many different theories reflecting a variety of underlying physical mechanism and one of the fundamental approaches is based on the generalized Langevin equation. It has been reported that the diffusion can be evaluated by the mean square displacement 〈∆ 2 ( )〉 ∝ , a subdiffusion for 0<α<1, a normal diffusion for α=1, a superdiffusion for α>1, and a ballistic diffusion for α=2 [20][21][22]. So far, most of the models deal with Brownian motion cases in a periodic potential, while the anomalous diffusion in active Brownian particles needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Now we choose x 1 , y 1 coordinates for dTOS whereas y 1 coordinate in case of mTOS for the interactions and assume that the coupling term vanishes at g  ¥. Hence, equations (12) and (13), become equations (14) and (15), and equations (16) and (17), respectively (same as discussed for equation (3)):…”
Section: Drive-response In Case Of Tosmentioning
confidence: 99%
“…Equations (14) and (15), depict that for dTOS, x 2 and y 2 depend only on their respective missing components as x 1 1 only drives x 2 and y 1 1 only drives y 2 which is similar to equation (3). On the other hand, equation (16), shows that in case of mTOS both x 2 and y 2 are driven by same y 1…”
Section: Drive-response In Case Of Tosmentioning
confidence: 99%
“…Understanding and controlling this collective dynamics is of both theoretical and practical significance [1,2]. Many methods have been proposed to enhance the network synchronizability, including the redistribution of the coupling strengths [3][4][5][6][7][8], the modification of the network structure [9][10][11][12][13], the flipping of link directionality [14][15][16][17] and so on. Each group of methods has its specific range of applications since different systems are under different technical constraints.…”
Section: Introductionmentioning
confidence: 99%